Potential of the mortgage housing lending market - N. I. Parusimova; D. A. Dobrin (Интеллект. Инновации. Инвестиции)
At present, mortgage housing lending in Russia continues to be one of the key drivers of growth in the construction sector and plays a significant role in improving housing affordability for the population. However, under conditions of increased uncertainty-driven by both external and internal factors, as well as technological and social changes – the Russian mortgage housing lending market is undergoing continuous transformation and facing new contemporary challenges. The scientific problem addressed in this article lies in the fact that, while preferential programs demonstrate an evident short-term positive effect, their long-term impact on the stability and balance of the mortgage housing lending market remains ambiguous. A comprehensive approach is required to account for numerous factors (macroeconomic conditions, banking strategies, structural features of the housing market, legislative framework, etc.) and to form a holistic understanding of the consequences of state measures aimed at improving housing affordability for specific social groups under inflationary pressure and tight monetary policy. The aim of the study is to identify causal relationships and determine the conditions for developing the potential of the mortgage housing lending market in the context of inflationary risks, a high key interest rate, and a wide range of government measures supporting access to housing for certain segments of the population. To assess the consequences of government support programs in the mortgage housing lending market, a combination of macroeconomic and sociological data analysis methods was employed, reflecting various aspects of the market’s development and its operating conditions. The scientific novelty of the study is expressed in the following results: the analysis and systematization of the diverse characteristics of the mortgage housing lending market; the identification of terminological inconsistencies in definitions that reflect the essence of the mortgage market; the refinement of the market concept based on an essentialist approach; the formulation of the market’s functional objectives from the perspective of participants; the establishment of causal relationships, functions, and specific features of the market; as well as the empirical analysis of its practical functioning. Based on the analysis of mortgage product dynamics from 2019 to 2024, several contradictory development trends were identified, which allowed for the justification of strategic directions to enhance the potential of the mortgage housing lending market under inflationary risks and high interest rates. The practical significance of the study lies in the proposed concrete measures: the transition to a hybrid model of the mortgage housing lending market; the strengthening of control over the targeted use of preferential loans; the consolidation of all preferential program operations under a single institution; and the adaptation of Russian banks’ mortgage product lines to increasing interest rate risks and changing consumer preferences. The need for further research into the mortgage housing lending market is driven by the ambiguous results observed during the analyzed period, heightened economic uncertainty, emerging challenges, and the current regulatory demands placed on market participants by the financial megaregulator.